2014
DOI: 10.1186/bcr3692
|View full text |Cite|
|
Sign up to set email alerts
|

Ubiquitin-conjugating enzyme complex Uev1A-Ubc13 promotes breast cancer metastasis through nuclear factor-кB mediated matrix metalloproteinase-1 gene regulation

Abstract: IntroductionUEV1A encodes a ubiquitin-conjugating enzyme variant (Ubc13), which is required for Ubc13-catalyzed Lys63-linked polyubiquitination of target proteins and nuclear factor κB (NF-кB) activation. Previous reports have correlated the level of UEV1A expression with tumorigenesis; however, the detailed molecular events leading to tumors particularly breast cancer and metastasis are unclear. This study is to investigate roles of different UEV1 splicing variants, and its close homolog MMS2, in promoting tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 46 publications
0
63
0
1
Order By: Relevance
“…Depletion of Ubc13 in these cells suppresses sister chromatid exchange and resensitizes these cells to cisplatin. Another recent study demonstrated that increased Uev1A levels can drive human breast cancer cell invasion and metastasis in mouse xenograft models in a manner that is dependent on Ubc13 43 . Ubc13 has also been shown to control breast cancer metastasis through the activation of a TAK1-p38 kinase 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Depletion of Ubc13 in these cells suppresses sister chromatid exchange and resensitizes these cells to cisplatin. Another recent study demonstrated that increased Uev1A levels can drive human breast cancer cell invasion and metastasis in mouse xenograft models in a manner that is dependent on Ubc13 43 . Ubc13 has also been shown to control breast cancer metastasis through the activation of a TAK1-p38 kinase 44 .…”
Section: Resultsmentioning
confidence: 99%
“…These tumors exhibit increased expression of Matrix Metalloproteinase-1 (MMP1) through activation of NFκB signaling 8 (Fig. 2), in which MMPs are involved in extracellular matrix degradation for tumor cell migration and invasion 9 .…”
Section: The Overexpression Of E2s Supports Aberrant Oncogenic Signalmentioning
confidence: 99%
“…Medzi E2 ubikvitín ligázy so známou úlohou v kontrole procesov progresie bunečného cyklu patrí UBE2N/ UBE2V1 enzým, ktorý katalyzuje polyubikvitináciu na Lys63. Aberantná polyubikvitinácia na Lys63 spúšťa aberantnú signalizáciu NF-κB, ktorá u ma-márneho karcinómu môže viesť k hyperaktivácii zápalu v makroprostredí nádoru [16,17].…”
Section: Ubikvitinácia V Súvislosti S Karcinogenézouunclassified